Fausses infinitives de but et mirativité - Geneviève Girard-Gillet (Anglophonia)
This article aims to analyse complex constructions with infinitival clauses which have hardly ever been taken into account, and whose infinitives imply, contrary to most infinitives, the validation of their semantic content. The constructions are the following ones: a) “Bush must have been drunk to have invaded Iraq”, which says that Bush did invade Iraq, and b) “he opened the door the find a dead cat on the doormat”, in which “he found a stray cat”, is validated. These constructions seem to mislead the addressee who expects with TO the description of a certain purpose, or of an intention, but soon understands that what is described is an illogical entailment or even a kind of “counter-result”, hence the possible mirative interpretation (DeLancey : 1997). After briefly summing up researches in Generative Grammar and in the theories of Enunciation, as regards infinitives, we shall analyse examples in context to understand their semantic dimension. It seems that Construction Grammars might be interesting to deal with them, as other sentences which also posit the validation of an eventuality cannot be decomposed as the combination of a matrix clause and an embedded one: “he was stupid to refuse the job” (Kertz: 2006), or “that will teach you to buy a Japanese car”. For the type a) sentences the utterer is expressing his derogatory point of view and giving his personal explanation to what occurred. The tone is hyperbolic, exaggerated. For the type b) sentences, it is destiny, or specific circumstances that seem to be playing tricks on a character. Whether he acts or not, he finds himself in a situation he had not expected, which is close sometimes to a kind of “counter-result”. In both cases the speaker thinks the situations are worth describing, because of their weird aspect, hence a possible mirative interpretation. The well-established cause-consequence relation is questioned, which is not the case with the following sentence, “he must have been intelligent to attain this lofty position”. The link between an intention and the expected result is not called into question either in “he opened the door to let John in.” The question is then: what are the semantic data that lead to the specific interpretations we are witnessing here?